Innovation in Agriculture: a Literature Review - Vargáné Dudás, Piroska; Szabó-Szentgróti, Gábor (Acta Carolus Robertus, 2024)
This article summarizes the promising opportunities and challenges of self-driving vehicles in agriculture. Through further research and development, these technologies may enable more sustainable, efficient and competitive agricultural practices in the future. Focused on understanding the factors influencing the adoption and adoption of transformative technology, we delve into the implications for farmers, industry stakeholders, and the future of sustainable agriculture. Using the keywords Industry 4.0, self-driving tractors, autonomous vehicles, agricultural tractors, automated agriculture, the literature review was prepared with the aim of getting a comprehensive picture of the use of self-driving tractors at the domestic and international level, and also gaining insight into the impact of Industry 4.0 and artificial intelligence on the in agriculture. We learn about self-driving tractors and the possible dangers of Industry 4.0 in agriculture. At the farmer level, the adoption of self-driving tractors represents a paradigm shift in the execution of agricultural tasks. Understanding the impacts on individual farmers, including changes in employment, skills required and potential socio-economic impacts, is essential. The introduction of autonomous technology may change traditional farming practices, so training programs and support mechanisms will be needed for farmers to adapt seamlessly to the new technological environment. It is vital to explore how this transition may affect the livelihoods, well-being and autonomy of individual farmers, ensuring that the benefits of self-driving tractors are equitable and inclusive.